2015
DOI: 10.1186/s40164-015-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes among HR+/HER2− metastatic breast cancer patients with multiple metastatic sites: a chart review study in the US

Abstract: BackgroundHormone receptor-positive, human epidermal growth factor receptor-2-negative (HR+/HER2−) is the most common type of metastatic breast cancer (mBC). While mBC patients generally have poor prognosis with limited progression-free survival (PFS) and overall survival (OS), those with multiple metastatic sites may have even worse clinical outcomes due to multiple organ involvement. This study aimed to compare clinical outcomes including PFS, time on treatment (TOT), and OS between HR+/HER2− mBC patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…In recent years, approximately 1.7 million new cases were diagnosed annually and 0.5 million deaths (per year) were caused by BC worldwide (3,4). In the US, BC caused approximately 231 000 newly diagnosed cases and about 40 000 deaths (17.3%) in 2015 (5,6). In Iran, BC is the most frequent cancer among malignancies in females and it caused 24.4% of all neoplasms with an incidence rate of 17.81 in 2006 (6).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, approximately 1.7 million new cases were diagnosed annually and 0.5 million deaths (per year) were caused by BC worldwide (3,4). In the US, BC caused approximately 231 000 newly diagnosed cases and about 40 000 deaths (17.3%) in 2015 (5,6). In Iran, BC is the most frequent cancer among malignancies in females and it caused 24.4% of all neoplasms with an incidence rate of 17.81 in 2006 (6).…”
Section: Introductionmentioning
confidence: 99%
“…Several concepts regarding the prognosis of HR+/HER2-metastatic patients have been considered important in evaluating survival after recurrence [11], and the current study was performed based on post-recurrent characteristics, especially the metastatic site. Previous studies have shown that first metastatic sites (single, multiple, liver, or other visceral metastases) are significantly related to survival after recurrence in HR+/HER2-patients [10][11][12][13], but there has been clinical diversity in the metastatic distribution patterns of both single metastasis and multiple metastases [25][26][27]. Therefore, we studied the prognosis of HR+/HER2-patients with single and multiple metastases separately.…”
Section: Discussionmentioning
confidence: 99%
“…However, the metastatic patterns of first metastatic sites, such as multiple metastases, immediately life-threatening disease, or rapidly progressive visceral metastasis or crisis, have not been clearly evaluated. Although previous real-world studies have demonstrated several significant prognostic factors of survival after recurrence [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], little regard has been given to the influence of the metastatic distribution patterns of first metastatic sites on patients' prognosis. We assumed that the metastatic distribution patterns should be analyzed in more detail for the relationship with survival after recurrence in HR+/HER2-patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ten of these were retrospective chart reviews [29,30,[32][33][34]37,38,41,44,45], two were physician surveys [31,46] and six were analyses of secondary databases (e.g., Surveillance, Epidemiology and End Results [SEER]-Medicare database, commercial claims) [35,36,39,40,42,43]. These studies examined a variety of therapeutic options, including endocrine therapy, chemotherapy and surgery.…”
Section: Overview Of Treatment Patterns Studiesmentioning
confidence: 99%
“…The authors concluded that cisplatin-gemcitabine combination chemotherapy is an effective regimen for patients with mTNBC. Xie et al [37] conducted a retrospective chart review study to compare clinical outcomes, PFS, TOT and OS between 699 HR-positive/HER2-negative mBC patients with multiple metastases versus those with a single metastasis. The authors concluded that patients with multiple metastases had significantly shorter PFS, TOT and OS than single metastasis patients, with similar outcomes in each line of therapy, highlighting the substantial clinical burden and unmet need for more efficacious treatments for the former group of patients.…”
Section: Overview Of Treatment Patterns Studiesmentioning
confidence: 99%